Basics of the rule of the Muslim Brotherhood in Egypt: Challenges of Reinforcing the Alternative System - Hasan Ahmadian (دولت‌پژوهی, 2019)
The purpose of this article is to examine the practical dimensions of the Egyptian Muslim Brotherhood's government experience on the basis of the theoretical foundations of this movement. Through this study, the author seeks to analyze the most important political debates over the one-year rule of the Brotherhood in Egypt and the consequences of its overthrow. In other words, explaining the critiques of the Brotherhood's practical approach and the practical and sometimes theoretical responses of the Brotherhood's government and its supporters are the subject of the article's discussion. As we know, the Muslim Brotherhood failed to achieve the democratic transition in Egypt, and its governmental experience led to the Egyptian democratic retreat. The twofold question of the paper is how the practical foundations of the Brotherhood's rule had its effect on its overthrow and what the consequences of this transformation would have on the Brotherhood movement as well as on Egyptian civil rule. In response, it is argued that the failure of pivotal principle of the Brotherhood model of rule, that is balancing, in the chaotic Egyptian environment led to its overthrow; The consequence of this overthrow, in addition to promoting the Brotherhood's pragmatism and increasing divisions, is spreading extremism and the difficulty of Brotherhood's return to power, which overall makes political reconciliation more difficult. Accordingly, the author, in a deductive process, relying on library data, has attempted to follow the process of change in the cause and effect of the research, explaining the reasons for the Brotherhood's functioning in government and its overthrow on the basis of its theory. The time frame of the article would be the Brotherhood's reign until the July 2013 coup and includes references to the aftermath.